The role of echocardiography in transcatheter aortic valve implantation - Onishi, Toshinari (Cardiovasc Diagn Ther, 2018)
Transcatheter aortic valve implantation (TAVI) is an effective and less invasive treatment for the increasing population of individuals with severe aortic stenosis (AS). Echocardiography is crucial in the assessment of AS patients from pre- to post-procedure. Transthoracic echocardiography (TTE) may be used to assess patient suitability for TAVI, as well as evaluate the severity of AS, the aortic valve complex, aortic valve morphology, mitral regurgitation (MR), and left ventricular function. Transesophageal echocardiography (TEE) is usually used as an intra-procedural monitoring tool to provide feedback during the procedure, to assess prosthetic valve function, and to detect complications rapidly before and after balloon aortic valvuloplasty (BAV) or transcatheter heart valve (THV) deployment. In this review, the role of echocardiography in the pre-, intra-, and post-TAVI procedure periods is described in detail.